1998
DOI: 10.1007/bf02375776
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alumina addition on the conductivity, microstructure and mechanical strength of zirconia — yttria electrolytes

Abstract: Abstract. The effect of alumina additions on the ionic conductivity and mechanical properties of 3 and 8 mol% Y203-ZrO 2 compositions has been investigated. Such materials are of interest for use in fuel cells and other similar applications. Sintered specimens were characterised by XRD, SEM, impedance spectroscopy, four -probe DC conductivity and mechanical strength measurements. Alumina additions had no affect on the conductivity degradation behaviour at 1000 ~ and the activation energy but resulted in an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Similarly a large reduction in the conductivity, as a result of alumina addition, was reported for ZrO2 -Y203 and ZrO2 -Sc203 systems by Badwal et al [18,29]. This is attributed in part to a decrease in the volume fraction of the conducting phase and in part to the additional constriction provided by alumina grains present at grain boundaries or in the bulk of the grain to migrating oxygen-ions [22,29,61]. Alumina remains mainly an inert phase in the electrolyte matrix.…”
Section: Effect Of Alumina Additions Alumina Is Added Tomentioning
confidence: 72%
See 2 more Smart Citations
“…Similarly a large reduction in the conductivity, as a result of alumina addition, was reported for ZrO2 -Y203 and ZrO2 -Sc203 systems by Badwal et al [18,29]. This is attributed in part to a decrease in the volume fraction of the conducting phase and in part to the additional constriction provided by alumina grains present at grain boundaries or in the bulk of the grain to migrating oxygen-ions [22,29,61]. Alumina remains mainly an inert phase in the electrolyte matrix.…”
Section: Effect Of Alumina Additions Alumina Is Added Tomentioning
confidence: 72%
“…The addition of up to 1 -2 wt% A1203 has very little effect on the mechanical strength, but several reports indicate some beneficial effect on the total conductivity of the material [67,68]. However, for larger additions of alumina, the conductivity reduction is much higher than that can be accounted for by an increase in the volume fraction of alumina [ 18,22,29,61]. Yamamoto et al [22], in the case of ZrO 2 -5c203 -A1203 system, reported a reduction in the conductivity by a factor of about two by the mere addition of 20 wt% alumina to 11 mol% Sc203 -ZrO 2.…”
Section: Effect Of Alumina Additions Alumina Is Added Tomentioning
confidence: 96%
See 1 more Smart Citation
“…its mechanical strength exceeds ca. twice the mechanical strength of the cubic phase zirconia [17]. At moderate temperatures below 700…”
Section: Introductionmentioning
confidence: 98%
“…Basing on literature data [17,18] as well as own studies [19] tetragonal zirconia: ZrO 2 +3 mol % Y 2 O 3 (3YSZ) can be promising solid electrolyte in IT-SOFC. Tetragonal zirconia shows excellent mechanical properties, i.e.…”
Section: Introductionmentioning
confidence: 98%